PTU-108 Prospective cohort to identify factors associated with diagnostic delay in patients with inflammatory bowel disease. Issue 2 (June 2019) - Walker, Gareth; Lin, Simeng; Thomas, Amanda; Chanchlani, Neil; Moore, Lucy; Hendy, Peter; Heerasing, Neel; Green, Harry; Mole, Sean; Bewshea, Claire; Goodhand, James; Kennedy, Nick; et al.
Abstract : Background: International cohort studies have previously identified Crohn's disease (CD), ileal disease, smoking, and age (<40 years old) as factors associated with a delay in diagnosis of patients with inflammatory bowel disease (IBD). Currently, there is a paucity of data looking at the factors influencing diagnostic delay specific to a UK population, where healthcare system is free at point-of-access. Hence, we conducted a prospective observational cohort study of patients referred to secondary care between January 2014 to December 2017. Methods: In total, 163 patients between the age of 18 and 46 years who first presented to their general practitioner (GP) with gastrointestinal symptoms from January 2014 were included in this study. Patients above the age of 46 were excluded due to the increased risk of colorectal cancer with increasing age. This was also the upper age limit recommended for faecal calprotectin use in the investigation of suspected IBD. In addition to baseline demographic data, our main outcome measure was time to overall diagnosis including time from onset of symptoms to GP presentation (patient delay), time of GP presentation to referral (primary care delay), and time of referral to diagnosis (secondary care delay). Results: The median time to diagnosis was 6.7 months [IQR 3.3–14.1], with no significant difference in time to diagnosis for IBD sub-types [CD, 9.8 months [IQR 5.5–18.5]; IBD-Unclassified, 7.0 months [IQR 4.5–8.5] and ulcerative colitis (UC), 5.2 months [IQR 2.9 −12.3] (p = 0.56 )]. The median time it took patients to present to their GP was 3.0 months [IQR 1.4–6.0]; median time for GP to refer to a gastroenterologist was 0.6 months [IQR 0.2–1.7]; and the median time from GP referral to diagnosis was 1.5 months [IQR 0.8–2.5]. On multivariable analysis, rectal bleeding (OR 0.33, 95% CI 0.15–0.71, p = 0.005) and abdominal pain (OR 2.49; 95% CI 1.13–5.89, p = 0.029) was negatively and positively associated with being in the upper quartile of patient delay. Urgent GP referrals (OR 0.14; 95% CI 0.05–0.36, p < 0.001) and triage by surgeons (OR 5.61; 95% CI 2.29–14.38, p < 0.001) had a negative and positive association with being in the upper quartile of secondary care delay, respectively. The use of faecal calprotectin or being triaged straight-to-test did not reach statistical significance. Conclusion: Referrals triaged urgently and by a gastroenterologist were associated with a reduction in secondary care diagnostic delay. Adopting a combination of primary care faecal calprotectin testing and secondary care straight-to-test may impact diagnostic delays.